2014
DOI: 10.3892/ijmm.2014.1917
|View full text |Cite
|
Sign up to set email alerts
|

The angiotensin-converting enzyme 2/angiotensin (1–7)/Mas axis protects the function of pancreatic β cells by improving the function of islet microvascular endothelial cells

Abstract: In the diabetic state, the local rennin-angiotensin system (RAS) is activated in the pancreas, and is strongly associated with islet dysfunction. The angiotensin-converting enzyme 2 (ACE2)/angiotensin (1-7) [Ang(1-7)]/Mas axis is a protective, negative regulator of the classical renin-angiotensin system. In this study, we assessed the role of the ACE2/Ang(1‑7)/Mas axis in pancreatic β cell survival and function. ACE2 knockout and wild-type mice were fed a high-fat diet for 16 weeks. We then performed terminal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 27 publications
1
37
0
1
Order By: Relevance
“…These findings were attributed to both MasR-dependent and MasR-independent mechanisms modulating insulin secretion via increased cAMP. In other studies using β-cells cocultured with islet endothelial cells (17) or diabetic rats (18), angiotensin-(1–7)–mediated improvements in GSIS were associated with enhanced islet endothelial cell function and pancreatic microcirculation. Given that our in vitro study design involved islet culture with peptides for up to 48 h and that the majority of endothelial cells are typically lost during this period in culture (27), it is unlikely that the islet microvasculature played a significant role in the increased insulin secretion we observed with angiotensin peptides.…”
Section: Discussionmentioning
confidence: 86%
“…These findings were attributed to both MasR-dependent and MasR-independent mechanisms modulating insulin secretion via increased cAMP. In other studies using β-cells cocultured with islet endothelial cells (17) or diabetic rats (18), angiotensin-(1–7)–mediated improvements in GSIS were associated with enhanced islet endothelial cell function and pancreatic microcirculation. Given that our in vitro study design involved islet culture with peptides for up to 48 h and that the majority of endothelial cells are typically lost during this period in culture (27), it is unlikely that the islet microvasculature played a significant role in the increased insulin secretion we observed with angiotensin peptides.…”
Section: Discussionmentioning
confidence: 86%
“…Ang-(1-7) has been found to attenuate STZ-induced diabetic renal injury through the Mas receptor [35]. A recent study has revealed that the Ang-(1-7)/Mas axis protects pancreatic ␤ cells from high-fat diet-induced dysfunction through improving the function of islet microvascular endothelial cells [11]. In agreement with this study, we found that Ang-(1-7) administration improved the survival of pancreatic ␤ cells in STZ-induced diabetic rats.…”
Section: Discussionmentioning
confidence: 97%
“…This aspect is really limiting, because diabetes and altered glucose homeostasis during a condition of severe pneumonia with SARS are reported as main factors of worse prognosis and death [152]. COVID-19 could also induce new onset diabetes, by augmenting insulin resistance and/or by a direct action [155] on the islets of Langerhans; supporting this view, previous studies have shown that ACE2 can be a therapeutic target to ameliorate microcirculation in the islets [156], and ACE2 is known to be expressed by pancreatic beta cells [157][158][159][160][161][162].…”
Section: Diabetes and Covid-19mentioning
confidence: 89%